IN-KIND AND/OR ENJOYMENT TAXES PROVIDE FAIR INCOME TAX TREATMENT FOR EMPLOYEES - Endah Purnama Sari Eddy; Verani Carolina (ZILLZELL MEDIA PRIMA, 2025)
Regulations regarding income tax on in-kind and/or enjoyment are now explained in detail in PMK No. 66 of 2023. These regulations are closely related to employees who are the most valuable asset in helping the company to be productive so that it can generate profits. The implementation of this policy caused controversy among the community. Some parties consider this policy as an excessive step by the government in optimizing tax revenue, while the government emphasizes that the regulation aims to clarify legal aspects and bring justice in the treatment of income tax for employees. This study aims to find out the community's response to in-kind and/or enjoyment tax policies that are considered to be aimed at creating tax justice for workers. The quantitative approach is used by the survey method to employees working in the city of Bandung. This research shows that in-kind and/or enjoyment taxes are not considered fair by most employees.